2007
DOI: 10.1080/03602550601152739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of β-Nucleators on iPP Crystallization and Morphology

Abstract: In this article, the effects of the b-nucleators WBG and WOT on the crystallization behavior and morphology of isotactic polypropylene (iPP) were investigated using a combination of differential scanning calorimetry (DSC), wide-angle X-ray (WAXD), polarized optical microscopy (POM) and atomic force microscopy (AFM). The results showed that the amount of b-form and the spherulite size decreased with increasing WBG contents. At about 0.15 wt. % WBG nucleator, the formation of the b-form was evidently observed. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Recently, Dou and Lu19–21 have found that some metallic salts of malonic acid possess β‐nucleating ability. Some complexes of rare earth metal (denoted as WBG) can also induce the formation of the β‐form 22–24. Recently, Zhang et al25 and Yang et al26 showed that the mixture of nano‐CaCO 3 and pimelic acid can be used as a two‐component β‐NA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dou and Lu19–21 have found that some metallic salts of malonic acid possess β‐nucleating ability. Some complexes of rare earth metal (denoted as WBG) can also induce the formation of the β‐form 22–24. Recently, Zhang et al25 and Yang et al26 showed that the mixture of nano‐CaCO 3 and pimelic acid can be used as a two‐component β‐NA.…”
Section: Introductionmentioning
confidence: 99%
“…In order to exclude the molecular weight effect, which is also present for the impact resistance of non-nucleated iPP homopolymers [62], the relative value of Δ NIS can be calculated by Equation (14). As Figure 7 shows, even in the worst-case increases by 300% can be achieved with CGNA-7588, while at least for the SSC-PPH a negative effect results from nucleation with WBG.…”
Section: Resultsmentioning
confidence: 99%
“…All mechanical parameters have been determined according to ISO standards using 10+2 measurements, discarding the extremes and giving relative standard deviations in the range of 5%. The relative effect of β-nucleation on impact strength (Δ NIS ) was calculated based on the following formula 14: (14) where NIS BN stands for the value of the β-nucleated polymer while NIS NN stands for the value of the nonnucleated base polymer. The calculation of Δ NIS was done for the values determined at 23°C.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some special techniques can be used to obtain the iPP with relatively high levels of b-phase, such as the temperature gradient method [11] , flow-induced crystallization [12][13][14] and adding specific nucleating agent [15][16][17][18][19] . Among them, the addition of some b-nucleating agents is an efficient and accessible method to obtain the iPP with relatively high level of b-phase.…”
Section: Study Of Micro-injectionmentioning
confidence: 99%